Antioxidative activity of 4-oxy- and 4-hydroxy-nitroxides in tissues and erythrocytes from rats - Wu Yong-Jie; Li Wen-Guang; Zhang Zhen-Ming; Tian Xuan (Acta Pharmacologica Sinica, 2016)
AIM: To compare the activities of antioxidation of 4-oxy- and 4-hydroxy-nitroxides in tissues and RBC from rats. METHODS: The homogenates of liver, heart, and kidneys of rats were used to determine malondialdehyde (MDA) formation using TBA colorimetric method. H2O2-caused hemolysis was measured spectrometrically. Superoxide anion from zymosan-stimulated neutrophils of rats was assayed by NBT reduction method. RESULTS: Nitroxide free radicals OTMPO and HTMPO inhibited MDA generation caused by .OH generation system (MIC 10.5 and 21 mumol.L-1, respectively), antagonized hemolysis induced by H2O2 (MIC: 338 and 168 mumol.L-1, respectively), but did not affect O2- formation from activated neutrophils. 1-Hydroxyl compounds OTMPOH and HTMPOH possessed similarly potent antilipoperoxidative activities. But nonfree radical OTMP and HTMP had no effect on peroxidation of tissues. CONCLUSION: Nitroxides exert their antilipoperoxidative effect by specifically scavenging .OH free radicals in biological system. Trapping of .OH free radicals by nitroxides is not by reduction of NO. group in nitroxides. Both NO. group and NOH group are essential active groups.